PENINGKATAN KEMAMPUAN KOMUNIKASI INTERPERSONAL PESERTA DIDIK DENGAN TEKNIK SOSIODRAMA PADA LAYANAN BIMBINGAN KELOMPOK - Luluk Ainun Nikmah; Anisa Dwi Pratanti; Amelia Dhamara Sofyati Halmahera; Evi Winingsih; Nurul Qomariyah (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
Interpersonal communication is one of the important skills in the school environment that is needed by students to be able to establish positive relationships with all members of the school and increase the effectiveness of learning. The aim of this research is to explore sociodrama techniques applied in effective group guidance services to improve students' interpersonal communication skills at SMA Negeri 1 Sumberrejo. Counseling Guidance Action Research (PTBK) was carried out as a method in this research involving eight students from class X-3 in two cycles. The results of the research showed that there was an increase in students' interpersonal communication skills after participating in group guidance services using sociodrama techniques. The use of the Wilcoxon test in data analysis showed that there was a significant difference between the pre-test score and the post-test score. The results of this research provide facts or empirical evidence about the benefits of sociodrama techniques in group guidance services as an effort to increase students' abilities in interpersonal communication skills.